2011
DOI: 10.1007/s00271-011-0280-6
|View full text |Cite
|
Sign up to set email alerts
|

Water savings, nutrient leaching, and fruit yield in a young avocado orchard as affected by irrigation and nutrient management

Abstract: This project was designed to determine the effect of fertilizer rate and irrigation scheduling on water use, nutrient leaching, and fruit yield of young avocado trees (Persea americana Mill. cv. Simmonds). Seven nutrient and irrigation management practices were evaluated: (1) irrigation based on crop evapotranspiration (ET) with 50% fertilizer at a standard rate (FSR); (2) ET irrigation with FSR (typical for avocado production in the area); (3) ET irrigation with 200% FSR; (4) irrigation based on exceedance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Water storage has constrained both economic and agricultural development in many arid and semi-arid regions. Instead of flood irrigation, which is regarded as wasting water resources, many water-saving irrigation technologies have been developed and promoted to enhance water productivity and to reduce water use [27]. Our results indicated that intermittent irrigation could also keep suitable water amount before sowing.…”
Section: Optimal Irrigation Strategymentioning
confidence: 57%
See 1 more Smart Citation
“…Water storage has constrained both economic and agricultural development in many arid and semi-arid regions. Instead of flood irrigation, which is regarded as wasting water resources, many water-saving irrigation technologies have been developed and promoted to enhance water productivity and to reduce water use [27]. Our results indicated that intermittent irrigation could also keep suitable water amount before sowing.…”
Section: Optimal Irrigation Strategymentioning
confidence: 57%
“…Therefore, we defined WUE and combined it with salt tolerance of a specific crop (sunflower), field water capacity and total irrigation water amount to determine the optimal irrigation strategy ( Table 5). Coefficient used to evaluate water effectiveness was usually defined as the crop yield divided by total water applied if there were crop growth [27] or the ratio of the quantity of water draining past the root zone to that infiltrated into the soil's surface in salt leaching condition [38]. Our study defined WUE coefficient to reflect the coupling effects of per irrigation amount on soil water, salt, and NO 3 --N storage (Eq.…”
Section: Irrigation Strategies Determinationmentioning
confidence: 99%
“…In order to improve water productivity and to minimise pollution, Kiggundu et al . (2012) evaluated several combined irrigation scheduling and nutrient management practices in southern Florida (25°20ʹN, 80°20ʹW; alt. 4 m).…”
Section: Irrigation Systemsmentioning
confidence: 99%
“…However, these production systems require more water use, yet agricultural water use faces competition from other sectors like municipal, industrial, and ecological [8] activities. Although smart irrigation water saving technologies (rain sensor, soil water sensor and evapotranspiration controller) [9][10][11] have been developed, Uganda's agriculture is dominated by small and medium scale farmers with national average land holding sizes of 1.1 ha [12]. These farmers cannot afford the investment and maintenance costs of systems such as smart irrigation equipment.…”
Section: Introductionmentioning
confidence: 99%